A Mathematical Model for the Study of the Effects of the Economic Cycle on the Real GDP Growth Rate through the Expectations-Adjusted Phillips Curve - Ferrentino, Rosa; Vota, Luca (International Journal of Economics and Financial Issues, 2020)
In this paper is presented a theoretical model finalized to explain the effects of the economic cycle on the real GDP growth rate of a given country’s economy towards a selected business partner. In other words, the present paper expose an innovative theoretical model, based on the expectations-adjusted Phillips Curve and on the Okun’s law, which proposes the existence of a relationship between the difference in the effective inflation rate and in the expected inflation rate of the national economy of a generic country (inflation gap), and the growth rate of the real GDP of the national economy and of its corresponding commercial partner, both determined by the different phases of the economic cycle. The two economies examined, for the purpose of empirical verification, are Germany and the group of the countries belonging to the euro area, considered, as a whole, as a single economy. The considered sample period ranges from the first quarter of 1999 to the first quarter of 2018. The result to which the authors arrive, appropriately verified with econometric models, indicates not only the existence, the significance and the robustness of the relationship established by it but also the ability of the model to predict, with good precision, the effects of the economic cycle on the real GDP growth rate, given the inflation gap. Keywords: Expectations-adjusted Phillips Curve, Okun’s Law, Business Cycle, mathematical models and methods. JEL Classifications: C02, C32, E32, E37 DOI: https://doi.org/10.32479/ijefi.9236